Radical Pedagogy in Doris Lessing's Mara and Dann. Issue 3 (27th May 2017) - Sperlinger, Tom
ABSTRACT: This article considers pedagogy as a consistent theme in Doris Lessing's fiction. It draws on a deleted prefatory note in the typescript to Mara and Dann, which states that the heroine is "consumed with a passion to learn and go to school." The article explores how Mara learns in a reimagined Africa after a future ice age. In the absence of formal schooling, a game is used in which children are asked repeatedly, "What did you see?" This game is compared to Henry James's use of a child's perspective in What Maisie Knew, to strategies for unveiling and "naming" the world in Paulo Freire's Pedagogy of the Oppressed, and to ideas about teaching in Idries Shah's The Sufis and Learning How to Learn . The article thus argues that radical and anticolonial approaches to learning are figured in Lessing's fiction, and in her Nobel lecture, as essential for human survival.